Greenland, view of Kjerulf Fjord through to Dicksons Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background on left; mountains forming eastern side of Unknown Valley. In center background: Hisinger Glacier [Hisinger Gletscher]. In background on right; mountains forming west side of Left Valley are here seen turning south to form Unknown Valley -- which is completely filled by Hisinger Glacier [Hisinger Gletscher]. In foreground pond-like lake sourced by Hisinger Glacier [Hisinger Gletscher] and out of which flows the stream of Left Valley. Photo taken from S.E. end of Left Valley, looking south.